Cocaine/crack use is not associated with fibrosis progression measured by AST-to-Platelet Ratio Index in HIV-HCV co-infected patients: a cohort study. Issue 1 (December 2017) - Martel-Laferrière, Valérie; Nitulescu, Roy; Cox, Joseph; Cooper, Curtis; Tyndall, Mark; Rouleau, Danielle; Walmsley, Sharon; Wong, Leo; Klein, Marina
Abstract Background Cocaine and crack use has been associated with HIV and HCV infections, but its consequences on HCV progression have not been well established. We analyzed the impact of cocaine/crack use on liver fibrosis progression in a cohort of HIV-HCV co-infected patients. Methods A Canadian multicenter prospective cohort study followed 1238 HIV-HCV co-infected persons every 6 months between 2003 and 2013. Data were analyzed from 573 patients with positive HCV RNA, not on HCV treatment, without significant liver fibrosis (AST-to-Platelet Ratio Index (APRI) <1.5) or history of end-stage liver disease at baseline, and having at least two study visits. Recent cocaine/crack use was defined as use within 6 months of cohort entry. Incidence rates of progression to significant fibrosis (APRI ≥ 1.5) were determined according to recent cocaine/crack use. Cox Proportional Hazards models were used to assess the association between time-updated cocaine/crack use and progression to APRI ≥ 1.5 adjusting for age, sex, HCV duration, baseline ln(APRI), and time-updated alcohol abuse, history of other drug use and CD4+ cell count. Results At baseline, 211 persons (37%) were recent cocaine/crack users and 501 (87%) ever used cocaine/crack. Recent users did not differ from non-recent users on gender, age, and CD4+ T-cell count. Over 1599 person-years of follow up (522 PY in recent users, 887 PY in previous users and 190 PY in never users), 158 (28%) persons developed significant fibrosis (9.9/100 PY; 95% CI, 8.3–11.4); 56 (27%) recent users (10.7/100 PY; 7.9–13.5), 81 (28%) previous users (9.1/100 PY; 7.1–11.1), and 21 (29%) never users (11.1/100 PY; 6.3–15.8). There was no association between ever having used or time-updated cocaine/crack use and progression to APRI ≥ 1.5 (adjusted HR (95%CI): 0.96 (0.58, 1.57) and 0.88;(0.63–1.25), respectively). Conclusions We could not find evidence that cocaine/crack use is associated with progression to advanced liver fibrosis in our prospective study of HIV-HCV co-infected patients.